1991
DOI: 10.1111/j.1365-2141.1991.tb04521.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐chromosome inactivation patterns using HPRT and PGK polymorphisms in haematologically normal and post‐chemotherapy females

Abstract: Clonal analysis using X-chromosome inactivation patterns of the hypoxanthine phosphoribosyl transferase (HPRT) and phosphoglycerate kinase (PGK) genes has been used in the assessment of haematological malignancies. In many analyses normal haemopoietic tissue or constitutive DNA from each individual has not been readily available and it has been assumed that when the ratio of the percentage of the two alleles remaining after differential methylation enzyme digestion is greater than 3/1 then an oligoclonal/monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 10 publications
3
82
0
Order By: Relevance
“…Vogelstein et al 32 found only three out of 81 (3.7%) normal females to have NRXI using the phosphoglycerate kinase (PGK) and hypoxanthine phosphoribosyl transferase (HPRT) Xinactivation probes. Recently, Gale et al 29 found significant NRXI in blood-derived cells in 23% of normal females using PGK and HPRT probes and 22% of females using M27␤, 30 which has been confirmed in numerous other studies. [33][34][35][36] Discordance in the incidence of NRXI was initially explained by the diversity of assays used, the different criteria for NRXI, and the small population sizes.…”
Section: Study Of the Normal Female Population: Unequal Lyonization Rmentioning
confidence: 64%
See 2 more Smart Citations
“…Vogelstein et al 32 found only three out of 81 (3.7%) normal females to have NRXI using the phosphoglycerate kinase (PGK) and hypoxanthine phosphoribosyl transferase (HPRT) Xinactivation probes. Recently, Gale et al 29 found significant NRXI in blood-derived cells in 23% of normal females using PGK and HPRT probes and 22% of females using M27␤, 30 which has been confirmed in numerous other studies. [33][34][35][36] Discordance in the incidence of NRXI was initially explained by the diversity of assays used, the different criteria for NRXI, and the small population sizes.…”
Section: Study Of the Normal Female Population: Unequal Lyonization Rmentioning
confidence: 64%
“…Although criteria for NRXI are arbitrary, an allelic Review L Busque and DG Gilliland 129 ratio у3:1 (which corresponds to the expression of 75% of one allele) has been widely accepted in the literature. 13,22,[29][30][31][32] Determination of the incidence of NRXI should be straightforward since it can be simply estimated by using X-inactivation assays in healthy females. Surprisingly, data obtained in the last 20 years by different investigators have been contradictory.…”
Section: Study Of the Normal Female Population: Unequal Lyonization Rmentioning
confidence: 99%
See 1 more Smart Citation
“…In neonates, the median value of this score was 59.5% in epithelial cells and 62.2% in blood cells, while in mothers, it was 60.9% and 65.7%, respectively. In accordance with the literature (42)(43)(44)(45), skewing was defined as equal to or greater than 75% of the predominant allele. Using this criterion, 7.6% (33 of 436)…”
Section: Cohortmentioning
confidence: 99%
“…Skewing is said to be present when the percentage of the predominant allele exceeds 74% (i.e., is ≥75%). This arbitrary definition has been used by a number of other groups (69)(70)(71)(72). A percentage of predominant allele between 90% and 100% is considered extreme skewing.…”
Section: Subjects Research Protocol Was Approved By the Ethical Resementioning
confidence: 99%